Analysis of the Implementation of the Universal Design for Learning Approach to Optimize Inclusive Student Learning Motivation - Safrina; Najmuddin; Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This study aims to explore the application of the Universal Design for Learning approach to optimize inclusive student motivation at the UPTD of SD Negeri 8 Makmur. The type of research used is quantitative descriptive. The data sources of this study are primary data and secondary data. Primary data were obtained from observations of student activities in the learning process. While secondary data are in the form of document data on the number of inclusive students at the UPTD of SD Negeri 8 Makmur. The subjects of this study were 4 inclusive students at the UPTD of SD Negeri 8 Makmur. Data collection techniques were through observation and documentation. Data collection tools were in the form of observation sheets. Data analysis techniques used percentage analysis. The results of the study showed that the learning motivation of inclusive students was classified as very good in terms of; a) the desire and desire to succeed by 93% in the very good category, b) the encouragement and need to learn with a score of 88% in the very good category, c) the existence of appreciation in learning with a score of 94% in the very good category, d) the existence of interesting activities in learning with a score of 93% in the very good category, and the existence of a conducive learning environment with an average score of 81% in the very good category. Learning activity activities were reviewed from the aspects of; a) Visual Activities, with a score of 93% in the Very Good category, b) Listening Activities with a score of 87% in the very good category, c) Oral Activities, with a score of 6% in the very poor category, d) Writing Activities with a score of 69% in the good category. The lowest achievement of inclusive student activities was in Oral Activities. This can be caused by several factors, such as limited communication skills, difficulty in understanding the subject matter, or lack of self-confidence.